2021
DOI: 10.3390/ijms22041930
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Crosslinked Sodium Alginate/Gelatin Wet-Spun Porous Fibers with Nisin Z for the Inhibition of Staphylococcus aureus-Induced Infections

Abstract: [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Tuning their properties via adjusting processing, solution, or environmental parameters, using a combination of natural and synthetic polymers with biodegradable characteristics, is considered the most reliable option. Complex architectures and configurations such as those highlighted in this review can generate systems that respond more intimately to local demands, while guaranteeing the safety of the user [13,118,122,163,168]. Indeed, by introducing drug delivery systems in which drugs are protected by an additional layer can prevent initial burst release and toxic side effects to the human body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuning their properties via adjusting processing, solution, or environmental parameters, using a combination of natural and synthetic polymers with biodegradable characteristics, is considered the most reliable option. Complex architectures and configurations such as those highlighted in this review can generate systems that respond more intimately to local demands, while guaranteeing the safety of the user [13,118,122,163,168]. Indeed, by introducing drug delivery systems in which drugs are protected by an additional layer can prevent initial burst release and toxic side effects to the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cylindrical shape of the fibers increases the surface area to volume ratio of the system, which allows drug release over broader area. Besides, the length and cross-sectional radius can be tuned according to the solution and processing parameters applied, contrary to spherical vesicles which tend to be more limited [162,163]. There are still not many reports on the production of more complex fiber architects for biomedical applications, due to the complexity of the structures and the number of parameters that have to be optimized.…”
Section: Tissue Engineering and Drug Delivery Applicationsmentioning
confidence: 99%
“…Sodium alginate (SA) is a linear polysaccharide derived from brown seaweed [ 55 ]. More specifically, SA is a derivative of alginic acid and is composed of α-1-guluornic (G) and 1,4-linked-β-D-mannuronic (M) monomers [ 55 ].…”
Section: Natural Biopolymer Scaffolds For Therapeutic Ev Deliverymentioning
confidence: 99%
“…In all cases, AMPs act against the microbial cells by disrupting the membrane/wall/envelope integrity, inhibiting proteins', nucleic acids', or other important compounds' synthesis, or by permeabilizing the microorganism and interacting with certain intracellular targets (Figure 2). One of the most important features of AMPs is their ability to act against microbial cells using a multi-hit strategy based on non-specific mechanisms of action, which tends to broaden their spectrum of antimicrobial action even against multi-resistant pathogens [8,17,28,29]. Recent studies have reported evidence of resistance mechanisms by pathogens against naturally occurring skin AMPs.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%